Notes on Humans as Prey of Reticulated Pythons Malayopython reticulatus (Serpentes: Pythonidae) in Indonesia - Iqbal, Muhammad; Sari, Diah Komala; Arifah, Nur; Widayanti, Gusti Ayu; Aprillia, Ina (BIO PALEMBANICA, 2025)
This study examines documented cases of humans being preyed upon or attempted to be preyed upon by Reticulated Pythons Malayopython reticulatus in Indonesia, spanning nearly a century from 1927 to 2025. Our study reveals 17 incidents, with snakes involved measuring between 5-8 meters in length. The victims' ages ranged from 13 to 90 years old, with 13 fatalities reported. Both males and females were affected, with 8 incidents involving men and 8 involving women. Sulawesi emerges as a hotspot for such encounters, accounting for a significant proportion of reported cases. This study highlights the importance of understanding human-python encounters and promoting a more harmonious coexistence between humans and wildlife in Indonesia. Keywords: human-wildlife coexistence, Indonesia, large snake, Malayopython reticulatus, Reticulated Python.